Development in Assay Methods for in Vitro Antimalarial Drug Efficacy Testing: A Systematic Review - Sinha, Shweta; Sarma, Phulen; Sehgal, Rakesh; Medhi, Bikash (Frontiers in Pharmacology, 2017)
The emergence and spread of drug resistance are the major challenges in malaria eradication mission. Besides various strategies laid down by World Health Organization, such as vector management, source reduction, early case detection, prompt treatment, and development of new diagnostics and vaccines, nevertheless the need for new and efficacious drugs against malaria has become a critical priority on the global malaria research agenda. At several screening stages, millions of compounds are screened (1,000–2,000,000 compounds per screening campaign), before pre-clinical trials to select optimum lead. Carrying out in vitro screening of antimalarials is very difficult as different assay methods are subject to numerous sources of variability across different laboratories around the globe. Despite this, in vitro screening is an essential part of antimalarial drug development as it enables to resource various confounding factors such as host immune response and drug-drug interaction. Therefore, in this article, we try to illustrate the basic necessity behind in vitro study and how new methods are developed and subsequently adopted for high-throughput antimalarial drug screening and its application in achieving the next level of in vitro screening based on the current approaches (such as stem cells).